Ecological Influences on Network Tie Dissolution in the Evolution of Affiliation Networks in the International Communication Association, 2009–2015. (6th February 2021) - Xu, Yu; Fulk, Janet; Monge, Peter
Abstract: This study examined the influences of ecological factors on the dissolution of affiliation ties in the International Communication Association (ICA). The affiliation network in this study represented the connections between ICA members and ICA divisions and interest groups. Guided by insights from organizational ecology and network theory, this research used a multilevel discrete-time event history analysis to test how ecological factors influenced active ICA members' decisions to drop affiliation ties. An empirical analysis was conducted using a longitudinal sample of 1, 282 active members and 23 divisions and interest groups from 2009 to 2015. The results showed that the likelihood of tie dissolution was significantly constrained by the length of an individual's organizational membership, the division or interest group's fuzzy density (generally considered as a proxy for legitimacy perceptions), and the group's contrast (one measure of the level of clarity vs ambiguity of a group's identity). Theoretical and practical implications are discussed.